2019
DOI: 10.5114/aoms.2018.76115
|View full text |Cite
|
Sign up to set email alerts
|

Labor induction in term nulliparous women with premature rupture of membranes: oxytocin versus dinoprostone

Abstract: Introduction Premature rupture of the membranes (PROM) refers to rupture of the fetal membranes prior to the onset of regular uterine contractions. Premature rupture of the membranes continues to be one of the most vexing issues of obstetrics due to increased maternal and fetal morbidity and mortality. Many studies have focused on how management should be in these cases. The purpose of this study was to investigate whether dinoprostone (PGE 2 analogue) administration is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 16 publications
(19 reference statements)
3
15
0
Order By: Relevance
“…Similarly, in the study by Güngördük, an incidence of 7.6% was reported for term PROM women with excessive uterine activity who received sustained‐release dinoprostone followed by oxytocin infusion 6 h later 12 . However, in our study, the percentage of women with uterine hyperstimulation was 20.6% in the PGE2 group, which was consistent with the result of the study by Nur Gozde Kulhan et al 14 In that study, it was found that the rate of uterine hyperstimulation was 22.3% in Turkish term PROM patients with dinoprostone pessary.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, in the study by Güngördük, an incidence of 7.6% was reported for term PROM women with excessive uterine activity who received sustained‐release dinoprostone followed by oxytocin infusion 6 h later 12 . However, in our study, the percentage of women with uterine hyperstimulation was 20.6% in the PGE2 group, which was consistent with the result of the study by Nur Gozde Kulhan et al 14 In that study, it was found that the rate of uterine hyperstimulation was 22.3% in Turkish term PROM patients with dinoprostone pessary.…”
Section: Discussionsupporting
confidence: 92%
“…The rates of cesarean delivery and induction failure were clearly decreased in the PGE2 group, which was consistent with the finding by Hingoro 13 . On the other hand, another study comparing vaginal dinoprostone with oxytocin infusion in the treatment of PROM with unfavorable cervixes at term found that the vaginal delivery rate within 24 h was smaller in patients with vaginal dinoprostone 14 . In the above research, patients with vaginal dinoprostone received no other labor induction methods, and not achieving active labor despite 12 h of continuous treatment with the vaginal dinoprostone was considered as induction failure, which was reported as the indication for cesarean delivery.…”
Section: Discussionsupporting
confidence: 88%
“…Muzorkevich et al [18] reviewed the role of oxytocin and prostaglandin derivatives in PROM and concluded that immediate labour induction by oxytocin provides an improved outcome status for patients with PROM at term.In a retrospective study evaluating the effect of dinoprostone and oxytocin in nulliparous women with term or preterm PROM on the delivery mode and delivery interval, the authors showed that the labour induction for PROM at term in nulliparous women with an unfavorable cervix resulted in a longer duration in the second stage, and an increased risk of cesarean delivery due to failure to progress, compared to those with intact membranes [19]. Oxytocin was found to be more successful in a study comparing the efficacy of oxytocin and dinoprostone in labor induction in the term, nulliparous, PROM pregnant women [20]. The inclusion of only nulliparous patients in this study may be associated with lower success rates.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons of methods of induction of labour following PROM were the focus of much of recent research related to PROM ( Prostaglandin pessary use was explored with mixed results in the studies by Güngördük et al (2012), Kulhan and Kulhan (2019), and Kunt et al (2010). Güngördük et al (2012) left the pessary in situ for up to six hours prior to commencing IV oxytocin, finding a higher rate of vaginal birth than oxytocin alone, with no difference in other maternal or neonatal outcomes.…”
Section: Methods Of Induction Of Labour Following Prommentioning
confidence: 99%